Morphological and clinical evaluation of prostatic urethra using modified sonourethrography with retrograde jelly injection. Issue 2 (29th November 2017) - Minagawa, Tomonori; Daimon, Hironori; Ogawa, Noriyuki; Saito, Tetsuichi; Suzuki, Toshiro; Domen, Takahisa; Nagai, Takashi; Ogawa, Teruyuki; Ishizuka, Osamu
Abstract : Objective: Using modified sonourethrography (mSUG) with retrograde jelly injection to precisely measure the morphological characteristics of the prostatic urethra, we assessed prostatic urethral morphology associated with clinical parameters of benign prostatic hyperplasia (BPH). Methods: BPH patients (n = 43) and control patients with localized prostate cancer (PC; n = 57) were imaged by mSUG before surgery. Using the seminal colliculus as a landmark, prostatic urethral angulation (PUA), sagittal urethral diameter, and anterior or posterior prostatic urethral length were measured. The International Prostatic Symptoms Score (IPSS) was also evaluated in all patients. The Bladder Outlet Obstruction Index (BOOI) was measured in BPH patients that could void in a pressure–flow study. Parameters were compared between BPH and PC patients, and correlations among morphological and clinical parameters were evaluated. Results: Prostatic urethras were clearly observed in all patients by mSUG. PUA, sagittal urethral diameter, and posterior urethral length were all greater in BPH than PC patients ( P < .05). Among all parameters examined, PUA had the strongest correlation with IPSS ( r = 0.56). Longitudinal urethral diameter showed the strongest correlation with BOOI, whereas PUA was not correlated with BOOI. Conclusions: Prostatic urethral morphology can be imaged precisely by mSUG. Morphometric measurements showed that increased PUA was strongly correlated with problematic urinary symptoms, and a flattened shape of the posterior urethra, such as extension of the sagittal urethral diameter, was correlated with urinary tract obstruction by BPH.